A legacy for the future. - Severin, Howie G.; Saturay, Ariel; Yap, April T.; Paz, Cynthia C.; Lim, Stanley; Papag, Ron M. ([Quezon City] AsiaVision Media Foundation and Foundation for the Philippine Environment, 1997)
Features the state of Philippine biodiversity and people's initiatives to protect the environment. Highlights the Banahaw, Palapag and Malindang experiences.
in English.